Homozygous carriers of APP A713T mutation in an autosomal dominant Alzheimer disease family - Conidi, Maria E. (Neurology, 2015)
OBJECTIVE: To report, for the first time, a large autosomal dominant Alzheimer disease (AD) family in which the APP A713T mutation is present in the homozygous and heterozygous state. To date, the mutation has been reported as dominant, and in the heterozygous state associated with familial AD and cerebrovascular lesions. METHODS: The family described here has been genealogically reconstructed over 6 generations dating back to the 19th century. Plasma β-amyloid peptide was measured. Sequencing of causative AD genes was performed. RESULTS: Twenty-one individuals, all but 1 born from 2 consanguineous unions, were studied: 8 were described as affected through history, 5 were studied clinically and genetically, and 8 were asymptomatic at-risk subjects. The A713T mutation was detected in the homozygous state in 3 patients and in the heterozygous state in 8 subjects (6 asymptomatic and 2 affected). CONCLUSIONS: Our findings, also supported by the β-amyloid plasma assay, confirm (1) the pathogenic role of the APP A713T mutation, (2) the specific phenotype (AD with cerebrovascular lesions) associated with this mutation, and (3) the large span of age at onset, not influenced by APOE, TOMM40, and TREM2 genes. No substantial differences concerning clinical phenotype were evidenced between heterozygous and homozygous patients, in line with the classic definition of dominance. Therefore, in this study, AD followed the classic definition of a dominant disease, contrary to that reported in a previously described AD family with recessive APP mutation. This confirms that genetic AD may be considered a disease with dominant and recessive traits of inheritance.